Prevalence and molecular characterization of Cryptosporidium spp. and Giardia spp. in environmental samples in Hanam province, Vietnam - Tram Thuy Nguyen; Traub, R.; Phuc Pham Duc; Hung Nguyen-Viet; Khuong Cong Nguyen; Cam Dac Phung; Dalsgaard, A. (Elsevier, 2016)
Cryptosporidium and Giardia are protozoan parasites that cause human diarrheal disease worldwide. This study was done to evaluate the prevalence and concentrations of these protozoa in environmental samples in Hanam, Vietnam and to assess potential contamination sources using molecular epidemiological tools. A total of 134 environmental samples were collected between February 2009 and July 2009, including 24 river water, 24 sewage, 32 fishpond water, 23 canal water, 26 vegetable and five composted waste samples. Samples were analyzed microscopically using an immunofluorescence method. Overall Giardia and Cryptosporidium were detected in 25.4% and 35.0% of samples analyzed, respectively. In water, a higher percentage of Cryptosporidium spp. (41.7%; 43/103) contamination was observed compared to that of Giardia spp. 28.2% (29/103). Both Giardia spp. and Cryptosporidium spp. were found contaminating vegetables at the same level, at 15.4% (4/26) each. Concentrations of Cryptosporidium in samples ranged from 10 to 1900 oocysts per 100 ml water or 100 g vegetable/composted waste sample with a median number of 100 oocysts per 100 ml/g. The concentration of Giardia cysts ranged from 10 to 1836 per 100 ml/g with a median of 60 cysts per 100 ml/g. Microscopy positive samples were subjected to PCR targeting the SSUrDNA gene for both Giardia and Cryptosporidium and the β-giardin gene for Giardia. PCR amplification and subsequent genetic characterization was successfully performed with 23/34 (67.6%) Giardia-positive samples and 15/47 (31.9%) Cryptosporidium-positive samples. Molecular characterization indicated the presence of Giardia duodenalis assemblages A and B and a high prevalence of Cryptosporidium suis. Although the latter being rare in humans, G. duodenalis assemblages A and B are potentially zoonotic. In conclusion, this study allowed sources of contamination and human health risks posed by Cryptosporidium and Giardia in environmental samples in Vietnam to be ascertained. More detailed studies are needed on the host range of different Giardia and Cryptosporidium species/subspecies, the potential for cross-species transmission, and risk and environmental factors involved in the exposure of the pathogen with the advent of molecular typing tools.